Обґрунтування конструктивної схеми пневморешітного сепаратора зерна - Васильковський, О. М.; Лещенко, С. М.; Нестеренко, О. В.; Петренко, Д. І.; Якименко, С.М.; Vasylkovskyi, O.; Leshchenko, S.; Nesterenko, O.; Petrenko, D.; Iakymenko, S. (ЦНТУ, 2021)
Статтю присвячено удосконаленню конструкції відцентрового пневморешітного сепаратора для розділення компонентів зернових сумішей. Базова конструкція задовільно виконує технологічний процес, однак має відносно великі вертикальні габарити за рахунок використання замкненої системи аспірації з подвійним очищенням зернової маси повітряним потоком. В роботі наведено концепцію удосконалення системи аспірації, що дозволить суттєво зменшити висоту, а також викладено методику проектного конструкторського розрахунку параметрів удосконаленої машини. The aim of the article is to improve the design of the original centrifugal grain separator. The separator is designed to separate the components of grain materials by size and aerodynamic properties. The basic design satisfactorily performs the technological process, but has large dimensions vertically. Reducing the size will simplify the design and reduce the cost of the machine. The article proposes to replace the double pneumatic cleaning of grain material with a single one. At the same time the car gets rid of the closed aspiration system. The closed aspiration system has operational advantages, however difficult adjustment reduces indicators of technological efficiency of pneumatic cleaning of grain. The original pneumatic cleaning system allows you to remove light impurities without creating significant air resistance, due to the lack of countercurrent movements. In addition, the use of an inclined pneumatic channel does not require the creation of high-speed airflow. As a result of the proposed improvement simplifies the structure and regulation of the separator, as well as reduces its size and weight. In addition to the modernization of the design of the pneumatic-sieve separator, the article presents the method of design engineering calculation of its basic geometric parameters. Depending on the specific capacity of the upper (ear) sieve and the characteristics of the grain mixture is determined by its length and angle. The remaining geometric parameters are derived from the above. Based on preliminary calculations, the following conclusions can be drawn. The use of the proposed scheme will reduce the height and weight of the centrifugal pneumatic sieve grain separator. Replacing the double air cleaning with a single one will simplify the adjustment of the machine. Experimental establishment of indicators of technological efficiency of the proposed separator will theoretically determine the dimensions and automate the design process of grain cleaning machines created by a similar scheme.
Substantiation of the Constructive Scheme of the Pneumatic-grain Separator
Keywords: сепаратор; зерно; обґрунтування; конструкція; розрахунок; параметри; аспірація; separator; grain; substantiation; design; calculation; parameters; aspiration